Protective role of metallothionein in acute lung injury induced by bacterial endotoxin. Issue 12 (24th November 2004) - Takano, H; Inoue, K; Yanagisawa, R; Sato, M; Shimada, A; Morita, T; Sawada, M; Nakamura, K; Sanbongi, C; Yoshikawa, T
Abstract : Background: Metallothionein (MT) is a protein that can be induced by inflammatory mediators and participate in cytoprotection. However, its role in inflammation remains to be established. A study was undertaken to determine whether intrinsic MT protects against acute inflammatory lung injury induced by bacterial endotoxin in MT- I/II knock out (−/−) and wild type (WT) mice. Methods: MT (−/−) and WT mice were given vehicle or lipopolysaccharide (LPS, 125 μg/kg) intratracheally and the cellular profile of the bronchoalveolar lavage (BAL) fluid, pulmonary oedema, lung histology, expression of proinflammatory molecules, and nuclear localisation of nuclear factor-κB (NF-κB) in the lung were evaluated. Results: MT (−/−) mice were more susceptible than WT mice to lung inflammation, especially to lung oedema induced by intratracheal challenge with LPS. After LPS challenge, MT deficiency enhanced vacuolar degeneration of pulmonary endothelial cells and type I alveolar epithelial cells and caused focal loss of the basement membrane. LPS treatment caused no significant differences in the enhanced expression of proinflammatory cytokines and chemokines nor in the activation of the NF-κB pathway in the lung between the two genotypes. Lipid peroxide levels in the lungs were significantly higher in LPS treated MT (−/−) mice than in LPS treated WT mice. Conclusions: Endogenous MT protects against acute lung injury related to LPS. The effects are possibly mediated by the enhancement of pulmonary endothelial and epithelial integrity, not by the inhibition of the NF-κB pathway.